Development and evaluation of shelf life of kodo millet added chicken meat nuggets - Dahriya, Sharda; Das, Keshab; Verma, Subhash Kumar; Patyal , Anil (Journal of Meat Science, 2024)
The present study was envisaged to develop kodo millet incorporated chicken meat nuggets and to explore the effect of kodo millet flour on the shelf life of chicken meat nuggets. The chicken meat nuggets were developed by using kodo millet flour at three different levels (T1-6%, T2-8% and T3-10%). Appearance/colour and flavour score, juiciness and overall palatability were found significantly higher (P < 0.05) for T1. On the basis of sensory scores, control and T1 were selected for further comparison and storage studies in refrigerated temperature for 28 days. TBA and SPC values increased significantly (P < 0.05) in both variants during storage. These values were found lower in treatment. Results of sensory evaluation studies during storage also revealed decrease in sensory scores in almost all occasions. T1 (treatment containing 6 % KMF) was rated higher for flavour, texture, juiciness and overall palatability throughout the storage period. It was concluded that functional chicken nuggets could be developed by replacing the chicken meat in standardized formulation at the level of 6 % kodo millet flour. The developed product maintains better physiochemical, microbiological and sensory qualities during refrigerated storage and was acceptable for 14th days.